PEMANFAATAN TEPUNG BERAS MERAH DALAM PEMBUATAN ROTI MANIS SEBAGAI UPAYA PENGURANGAN PENGGUNAAN TEPUNG TERIGU (Utilization Of Brown Rice Flour in the Making of Sweet Bread to Reduction using of Wheat Flour ) (Jurnal Teknologi Pangan, 2017)
ABSTRACTSweet bread is a product that is the result of roasting process dough that has beenfermented with the main ingredient wheat flour. The wheat flour is obtained from wheat flouras the main raw material that has to be imported. In order to reduce the use of wheat flour inmaking bread, then it is added with the brown rice flour whichbecomes substitution for wheatflour. Brown rice flour is gluten-free flour, brown rice are produced from organically farmed.This study aimed to acknowledge the effect of substitution of brown rice flour and glutenaddition to the quality of the physical, chemical, organoleptic and acknowledge the besttreatment combination.This research usedCompletely Randomized Design(CRD) arrangedin factorialconsisting of 2 factorsand 3replications. The first factors is the substitutionofbrown riceflour10%, 20%, 30% and thesecondfactoris the addition ofgluten2%, 4%,6%.The results showed that the best treatment isthesubstitution of brown rice flour 10% (w /w) and the addition of 6% gluten that produces sweet bread with criteria: 27.282% watercontent, protein content 9.761%, 43.030% starch content, the levels of β-carotene 1.91mg/100g, 648.160% volume expansion, 0.321% pore number, organoleptic value: 147.5texture; colors 110.5; flavor 149.5; aroma 137.5.Keywords: wheat flour, red rice flour, gluten ABSTRAKRoti manis adalah produk olahan yang merupakan hasil proses pemangganganadonan yang telah di fermentasi dengan bahan utama adalah tepung terigu, dimana tepungterigu diperoleh dari gandum yang sebagai bahan baku utama ini harus diimpor. Dalamrangka untuk mengurangi penggunaan tepung terigu dalam pembuatan roti maka ditambahkan tepung beras merah yang menjadikan subtitusi terhadap tepung terigu. Tepungberas merah adalah tepung bebas gluten, dihasilkan dari beras merah yang dibudidayasecara organik.Penelitian ini bertujuan untuk mengetahui pengaruh subtitusi tepung berasmerah dan penambahan gluten terhadap kualitas kimia, fisik dan organoleptiksertamengetahui kombinasi perlakuan terbaik.Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) yang disusun secarafaktorial yang terdiri dari 2 faktor dan diulang 3 kali. Faktor I adalah subtitusi tepung berasmerah 10%, 20%, 30% dan faktor II adalah penambahan gluten 2%, 4%, 6%.Hasil penelitian menunjukkan bahwa perlakuan terbaik adalah pada perlakuansubstitusi tepung beras merah10% (b/b) dan penambahan gluten 6% yang menghasilkanroti manis dengan criteria kadar air 27,282%, kadar protein 9,761%, kadar pati 43,030%,kadar β-karoten 1,91 mg/100g, volume pengembangan 648,160%, jumlah pori 0,321%, nilaiorganoleptik tekstur147,5 ; warna110,5; rasa 149,5 ; aroma 137.Keywords: tepung terigu, tepung beras merah, gluten